Balance between community assembly processes mediates species coexistence in agricultural soil microbiomes across eastern China - Jiao, Shuo; Yang, Yunfeng; Xu, Yiqin; Zhang, Jie; Lu, Yahai (The ISME Journal, 2020)
Revealing the linkages between community assembly and species coexistence, which is crucial for the understanding of ecosystem diversity and functioning, is a fundamental but rarely investigated subject in microbial ecology. Here we examined archaeal, bacterial, and fungal community assembly in adjacent pairs of maize (water-unsaturated) and rice (water-saturated) fields across different habitats and regions throughout Eastern China. The high-throughput sequencing dataset was analyzed by variation partitioning, null model, and neutral community model analyses. We demonstrated that microbial community assembly was governed more by species sorting than by dispersal limitation in maize fields, and to a lesser extent in rice fields. The relative importance of species sorting in maize soils was greater at low latitudes than at high latitudes, while rice soils exhibited an opposite trend. Microbial co-occurrence associations tended to be higher when communities were primarily driven by dispersal limitation relative to species sorting. There were greater community dissimilarities between maize and rice soils in low-latitude regions, which was consistent with the higher proportion of negative edges in the correlation networks. The results indicate that a balance between species sorting and dispersal limitation mediates species coexistence in soil microbiomes. This study enhances our understanding of contemporary coexistence theory in microbial ecosystems.